1985
DOI: 10.1007/bf00252745
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for the quantification of the in vivo kinetics of a representative population of 111In-labelled human platelets

Abstract: The recommended and commonly used methods for the isolation of platelets from whole blood do not harvest a representative platelet population. There is evidence that these methods may result in the loss of a functionally more active platelet subpopulation. We describe a method whereby a completely representative population of platelets was isolated from the whole blood of 28 normal human volunteers by repeated washing of platelets from the red-cell layer. The harvesting efficiency was 98.3% +/- 2.8%. The plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Uptake values on the 1st day after administration of the labelled platelets were found to be 7.4%_+ 3.0% in the liver and 43.2% _+ 14.8% in the spleen. Comparing these results with values in normal humans (Wessels et al 1985), it may be concluded that the hepatic uptake of labelled platelets is decreased in liver cirrhosis, while the splenic uptake is increased. Uptake values on the 7th day, when the state of platelet destruction was known, were found to be 13.6% _+ 8.2% in the liver and 53.7% ± 14.3% in the spleen.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Uptake values on the 1st day after administration of the labelled platelets were found to be 7.4%_+ 3.0% in the liver and 43.2% _+ 14.8% in the spleen. Comparing these results with values in normal humans (Wessels et al 1985), it may be concluded that the hepatic uptake of labelled platelets is decreased in liver cirrhosis, while the splenic uptake is increased. Uptake values on the 7th day, when the state of platelet destruction was known, were found to be 13.6% _+ 8.2% in the liver and 53.7% ± 14.3% in the spleen.…”
Section: Discussionmentioning
confidence: 65%
“…Liver cirrhosis if often associated with anemia, and venesection of such a large volume of blood is therefore ethically unacceptable. Tharkur et al (1976) reported a new technique of labelling platelets with indium-111 oxine, in which only a small amount of blood was required because of a high labelling ratio, and several studies have been performed using this technique (Dewanjee et al 1981;Wessels et al 1985;Toghill and Green 1983).…”
Section: Introductionmentioning
confidence: 99%
“…1 -9 Although these measurements are quantitative and objective, they are not readily interpreted in terms of rates of thrombus formation and dissolution. For example, platelet survival studies, which reflect all mechanisms of platelet utilization, cannot discriminate the interdependent processes of sensecent platelet removal, 16 normal platelet utilization for the maintenance of vascular integrity, 10 and additional components of platelet destruction due to vascular disease. Similarly, measurements of localized platelet depo-sition by scintillation camera imaging or other methods may have little relation to overall platelet turnover.…”
mentioning
confidence: 99%
“…Autologous platelets were labelled with " 'Intropolone and the MPLS estimated as previously described (19,20). Radioactivity of blood samples in EDTA was determined in a well-type scintillation counter (Packard Auto-gamma 5650, United Technologies, Packard).…”
Section: Platelet Kineticsmentioning
confidence: 99%
“…This is an indirect estimate of platelet production. The in vivo distribution and sites of sequestration of labelled platelets was quantified as described in detail (20,23). Briefly, anterior and posterior images with and without a posterior and anterior placed standard radioactivity source were acquired of the thorax and abdomen using a large field of view scintillation camera interfaced with a data processing system.…”
Section: Platelet Kineticsmentioning
confidence: 99%